As narradoras: entre escutas, diálogos e sensibilidades de escrevedoras de cartas e arte/educadoras - Ribolli, Mariana Vidal [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The journey through stories has always been exciting to me. 12 million people live in the big city of Sao Paulo and I deduce that approximately almost a thousand of them pass by me daily. The possibilities of narratives that intersect with yours are endless. But do people really care about these narratives in this hustle and bustle of the modern world? Since I was a child I have always looked at stories like a miner looks for gold and I owe that to my grandparents. This work comes from my desire to continue searching for narratives in a poetic and sensitive way, even in a western society, which is daily saturated by information. My meeting with nine letter writers and the meeting of their narratives with four art/educators’s narratives resulted in this audiovisual documentary experiment and in this sensitive writing piece about the description of the video creation process, in which listening and narratives compose the essence of this Final Honors Project.

A travessia por histórias sempre me foi algo entusiasmante. Na grande cidade de São Paulo vivem 12 milhões de pessoas e deduzo que, aproximadamente, quase mil delas passam por mim diariamente. As possibilidades de narrativas que cruzam com a sua são infinitas. Mas, as pessoas realmente se importam com essas narrativas na correria do mundo moderno? Desde criança sempre fui uma garimpeira de histórias e devo isso aos meus avós. Esse trabalho vem com meu desejo de continuar procurando e pesquisando narrativas de forma poética e sensível, mesmo estando em uma sociedade ocidental, que é engolida diariamente pela informação. Meu encontro com nove escrevedoras de cartas, que possibilitaram o encontro de suas respectivas narrativas com as de quatro arte/educadoras, resultaram em um experimento documental audiovisual e nesta presente escrita sensível sobre a descrição do processo de criação do vídeo, no qual escutas e narrativas compõem a essência desse Trabalho de Conclusão de Curso.
The narrators: between listening, dialogue and sensibilities of letter writers and art/educators
Keywords: Arte narrativa; Narrativas pessoais; Cartas; Vida urbana